2003
DOI: 10.1300/j052v23n01_01
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Nutritional Status of Older Adult Homeless Women

Abstract: A pilot study was conducted to identify eating patterns, food sources, and nutritional problems among a limited population of older homeless women located in a large urban area. Most of these women's food came from shelter meals, and their food intake was inadequate for most nutrients. The availability of fruits, vegetables, dairy products, and whole grains was very limited. Foods high in saturated fats and simple carbohydrates provided most of their caloric intake. Although some women were obese, most were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…However, it may be that meal programs contribute to food insecurity. Many homeless individuals may depend on or use charitable food programs [ 11 , 21 , 49 ], but evaluations of such programs have revealed that their meals may be inadequate both in terms of the quantity/frequency [ 50 , 51 ] and nutritional content provided to meet their needs [ 50 , 52 ]. For example, the current system of food provision to individuals who are food insecure in Canada, largely provided by charitable organisations, has been characterised as inadequate and poorly coordinated [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be that meal programs contribute to food insecurity. Many homeless individuals may depend on or use charitable food programs [ 11 , 21 , 49 ], but evaluations of such programs have revealed that their meals may be inadequate both in terms of the quantity/frequency [ 50 , 51 ] and nutritional content provided to meet their needs [ 50 , 52 ]. For example, the current system of food provision to individuals who are food insecure in Canada, largely provided by charitable organisations, has been characterised as inadequate and poorly coordinated [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Luder et al [49] revealed that homeless people’s diets are often high in saturated fats and cholesterol and inadequate in essential nutrients, contributing to adverse lipid profiles. Another [50] study of nutritional status among a group of adult homeless women found a similar trend: recommended daily allowances [RDAs] were commonly exceeded for sodium and saturated fats, both of which are independently associated with increased CVD risk [51,52]. Furthermore, if the homocysteine theory of arteriosclerosis [53] proves to be valid, then the vitamin and mineral deficiencies commonly found in the homeless, including vitamins B-6, B-12 and folate could also indirectly increase CVD risk through elevation of homocysteine levels.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have long demonstrated that shelter and soup kitchen meals have a high prevalence of inadequate or imbalanced nutrient, vitamin and mineral content (6,7) . The nutritional quality of food served to homeless individuals in the USA is often of poor nutritional value.…”
mentioning
confidence: 99%
“…The nutritional quality of food served to homeless individuals in the USA is often of poor nutritional value. Studies have long demonstrated that shelter and soup kitchen meals have a high prevalence of inadequate or imbalanced nutrient, vitamin and mineral content ( 6 , 7 ) . In Boston, for example, shelters commonly receive and serve an abundance of leftover pastries, pizzas and desserts donated by local restaurants.…”
mentioning
confidence: 99%
See 1 more Smart Citation